CCPS 8(3), December 2022, Focus – Under the Shadow of Vladimir Putin’s Irredentist War: How Russia’s Invasion of Ukraine Impacts China’s Global and Regional Relations - Emile Kok-Kheng Yeoh (ed.) (Contemporary Chinese Political Economy and Strategic Relations: An International Journal, 2022)
Contemporary Chinese Political Economy and Strategic Relations: An International Journal (CCPS), Vol. 8, No. 3, December 2022 (Focus – Under the Shadow of Vladimir Putin’s Irredentist War: How Russia’s Invasion of Ukraine Impacts China’s Global and Regional Relations), pp. 367-861 (495 pp. + xvii).